“Who does this History curriculum want you to be?”: Representation, School History and Curriculum in Zimbabwe (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This paper looks critically at representation in the history curriculum of Zimbabwe in relation to the production of subjectivity and identity that the government hopes will fulfil the quest for nationhood. It finds that content selection is skewed towards promoting a dominant group while syntactic knowledge is manipulated to make students be what the state wants them to think and be. Furthermore, the examinations reinforce the dominance of a single group by privileging metaphors that emphasize a selective narrative. The paper argues that the adoption of critical modes of address that promote critical pedagogic practice can help both the teachers and their students transcend the narrow specifications of the nationalist curriculum. This requires that the school history curriculum should be treated as a political performance which must be appraised beyond the written surface of its textuality as to uncover the unconscious and constraining representations in it. In this way teachers are likely to contribute new sentences, not oft-repeated ones, to that unending dialogue between the present and the past which is history.
Keywords: History curriculum; Nation-state; Identity; Critical pedagogic practice; Modes of address; Zimbabwe